Comparison of ambient air survival of Mycobacterium tuberculosis clinical strains associated with different epidemiological phenotypes - Katherine Klein; Zhenhua Yang (International Journal of Mycobacteriology, 2014)
This study compared the ambient air survival of two clinical strains of Mycobacterium tuberculosis that had caused significantly different numbers of cases in the same population. No difference in the survival ability between the two strains was found. However, a significant difference was observed in colony morphology between the two strains. These findings provide new insight into potential microbial determinants for the occurrence of large clusters of tuberculosis cases in a population.